Collaborative networks as incubators of dynamic virtual organizations: a case study of the emerging MAP sector - Da Silva, J.; I. Almeida (International Journal of Manufacturing Technology and Management, 2017)
This research aims to understand what development is needed in the Medicinal and Aromatic Plants (MAP) sector to strengthen the operations policy arguments supported by a reference model borrowed from the European Collaborative networked Organizations LEADership project. The adequacy of existing IT support to the social network to create a Virtual Organisation (VO) Breeding Environment (VBE) is also assessed by a qualitative exploratory case study addressing the EPAM (Entrepreneurship-in-MAP project) IT-platform. Data were collected from the EPAM website and multiple secondary sources. Contributions to practice include setting critical success factors, discussing management roles and checking the IT-platform state-of-the-art to set up the MAP-VBE in EPAMs scope. While introducing the neutral mediator role constitutes a contribution to the theory, innovative insights into MAP structuring would promote Operations Management research on VO incubation/formation in nascent/emerging contexts of an experimental/entrepreneurial nature. Failure to establish trust among VBE participants is the most feared limitation.